2021
DOI: 10.3390/ijms22147296
|View full text |Cite
|
Sign up to set email alerts
|

CD91 Derived Treg Epitope Modulates Regulatory T Lymphocyte Response, Regulates Expression of Costimulatory Molecules on Antigen-Presenting Cells, and Rescues Pregnancy in Mouse Pregnancy Loss Model

Abstract: The loss of immune tolerance to fetal antigens may result in reproductive failure. The downregulated number and activity of T regulatory lymphocytes, which are critical for the establishment of immune tolerance to fetal antigens, during pregnancy may lead to miscarriage. The adoptive transfer of Tregs prevents fetal loss in abortion-prone mice. Recently, we demonstrated that the administration of tregitopes, which are short peptides found in human and mouse immunoglobulins (IgGs), decreased the incidence of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…12 Regulation of CD91 can improve DC's tolerogenic properties to improve pregnancy in AP mice. 13 Our data are in line with those reports by showing dysfunction of tDCs in AP mice.…”
Section: Discussionsupporting
confidence: 93%
“…12 Regulation of CD91 can improve DC's tolerogenic properties to improve pregnancy in AP mice. 13 Our data are in line with those reports by showing dysfunction of tDCs in AP mice.…”
Section: Discussionsupporting
confidence: 93%
“…According to our results, the expression of both miR-155 and miR-146a seems to be reduced in patients with recurrent EPL, which may be related to the reduced number of Treg cells in the patients. Studies have shown that the number of Treg cells decreased in both mouse pregnancy loss model and patients with unexplained recurrent pregnancy loss [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the expression of both miR-155 and miR-146a seems to be reduced in patients with recurrent EPL, which may be related to the reduced number of Treg cells in the patients. Studies have shown that the number of Treg cells decreased in both mouse pregnancy loss model and patients with unexplained recurrent pregnancy loss [28,29]. The miR-106b-93-25 cluster plays a crucial role in the regulation of the TGF-β signaling pathway, and it is an essential cytokine in the induction of Foxp3 production by Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…administration of LRP1-derived peptide into abortion-prone pregnant mice significantly decreased the abortion rate by increasing immunomodulating Tregs. Increased LRP1-derived peptide-Treg expansion coupled with upregulated IL2 and IL10 in mouse serum, as well as decreased expression of co-stimulatory molecules of APCs resulted in successful pregnancies in mice ( 100 ).…”
Section: T Cellsmentioning
confidence: 99%